STUDENTS’ PERCEPTIONS OF ENGLISH ORAL COMMUNICATION USAGE DURING THEIR PRACTICE LEARNING PROGRAM - Rini Fitria; Salwa Salwa (INOVISH JOURNAL, 2018)
The objective of the research was to investigate students’ perceptions of English oral communication usage during their practice learning program. This research was quantitative and qualitative research. The population in this study was semester 7 (seven) students of English Study Program of STAIN Bengkalis. A set of questionnaire was distributed to 25 students regarding their perceptions on oral communication usage during their practice learning program and a face to face interview was carried out to 6 students. In this research, measurement of these statements using the Likert scale ranging from 1 = Strongly Disagree, 2 = Disagree, 3 = Undecided, 4 = Agree and 5 = Strongly Agree. The data collected was analyzed using SPSS 22 to know the normality, validity, and reliability of the instrument. The results of this study showed that students had positive perceptions on English oral communication usage during their practice learning program.